Clozapine Serum Concentrations Are Disrupted by SARS-CoV-2 Vaccinations - Kersting, Xenia A. K.; Momtahen, Nicoletta; Lieb, Klaus (Case Reports in Psychiatry, 2023)
This paper reports the case of a 27-year-old man with paranoid schizophrenia who was finally stabilized on clozapine medication. After vaccination against severe acute respiratory syndrome coronavirus 2, serum levels of clozapine increased. It is well established that immune responses can trigger cytokine cascades affecting drug metabolism, which, in the case of clozapine treatment, can lead to severe intoxication.